Pendidikan Karakter dalam Membangun Moderasi Beragama Generasi Milenial - Eka Selvi Handayani; Ardiyanto Saleh Modjo; Achmad Junaedi; Trisna Rukhmana; Al Ikhlas (Departement of Mathematics Education, 2024)
Character plays a crucial role in shaping religious moderation in the millennial generation. This research investigates the role of character education in forming attitudes of tolerance, respect for differences, and understanding of religious moderation in the millennial generation. Through a qualitative approach involving in-depth interviews, participatory observation, and document analysis, the findings show that character education activities in schools, such as group discussions and extracurricular activities, have a positive impact in shaping the character of the millennial generation who are moderate in religion. Character education programs that emphasize the values ​​of diversity, harmony and respect for religious plurality have also proven effective in building a strong foundation for religious moderation. In conclusion, character education is a vital instrument in supporting the development of religious moderation in the millennial generation, by emphasizing the need for collaboration between schools, government, families and society.